The Monarch Butterfly as a Model for Understanding the Role of Environmental Sensory Cues in Long-Distance Migratory Phenomena - Guerra, Patrick A. (Frontiers in Behavioral Neuroscience, 2020)
The awe-inspiring annual migration of monarch butterflies (Danaus plexippus) is an iconic example of long-distance migratory phenomena in which environmental sensory cues help drive successful migration. In this mini-review, I begin by describing how studies on monarch migration can provide us with generalizable information on how sensory cues can mediate key aspects of animal movement. I describe how environmental sensory cues can trigger the development and progression of the monarch migration, as well as inform sensory-based movement mechanisms in order to travel to and reach their goal destination, despite monarchs being on their maiden voyage. I also describe how sensory cues can trigger season-appropriate changes in migratory direction during the annual cycle. I conclude this mini-review by discussing how contemporary environmental challenges threaten the persistence of the monarch migration. Environmental challenges such as climate change and shifting land use can significantly alter the sensory environments that monarchs migrate through, as well as degrade or eliminate the sources of sensory cues that are necessary for successful migration.